Studi di fisiognomica amorale: istantanee di ibridazione (Altre Modernità, 2021)
As part of the reflections on animal studies, contemporary art makes its own contribution. Karin Andersen’s research is exemplary in this sense. As an artist and theorist, Andersen proposes a renewed vision of the world far from anthropocentrism in which man recognizes and welcomes otherness, also tracing the ways in which our culture is indebted to the biosphere. The article proceeds through the analysis of some works starting from Studi di fisiognomica amorale, real snapshots of hybridization which offer access to a positive and equal relationship between man and animal.
Keywords: Karin Andersen; contemporary art; theriomorphism; physiognomy; human-animal hybridization